Cross-sectional analysis of cannabis use at work in the USA: differences by occupational risk level and state-level cannabis laws - David Hammond; Ava Kucera (BMJ Public Health)
Objective To examine the prevalence of workplace cannabis use, including by state-level cannabis laws, occupational risk and medical cannabis use.Methods Data are cross-sectional from wave 6 (2023) of the International Cannabis Policy Study (ICPS) and include 26 458 respondents aged 16–65 years from the USA. Separate regression models were run analysing workplace cannabis use across: (1) state-level cannabis laws and occupational risk, (2) reasons for cannabis use and (3) medical cannabis authorisation. All models were adjusted for sociodemographic characteristics.Results Overall, 7.4% of workers and 21.5% of past 12-month cannabis consumers reported using cannabis at or within 2 hours of starting work in the last 30 days. Workplace cannabis consumption was highest among workers in states with ‘recreational’ cannabis laws (8.5%) compared with states with medical (6.3%; adjusted OR (AOR)=1.45, p=0.006) or illegal laws (6.2%; AOR=1.06, p=0.005). Workers in high-risk jobs were more likely to use cannabis at work (11.4%) than those in lower risk jobs (5.8%; AOR=1.58, p<0.001). Workplace cannabis use was also greater among cannabis consumers who use cannabis for medical versus recreational (29.4% vs 15.6%; AOR=2.35, p<0.001) or mixed reasons (24.2%; AOR=1.78, p=0.007); the same was true for consumers who reported having medical cannabis authorisation (39.0%) versus those without authorisation (17.4%; AOR=2.66, p<0.001).Conclusions Reported cannabis use at work was most prevalent in states with recreational legalisation, particularly among individuals with medical cannabis authorisation and those who work higher risk jobs. Longitudinal research should examine the individual and occupational-level factors associated with workplace cannabis use.